Impact of structural design criteria on the comfort assessment of tall buildings. Issue 180 (September 2018) - Johann, Ferrareto A.
Abstract: Assessing tall building oscillation due to wind-induced motion is a multidisciplinary task that involves knowledge from several fields of study, including: structural engineering, wind engineering, reliability, and even human physiology. With the modern high strength structural materials and the latest tendencies in tall buildings construction, new structural systems have become slender and new buildings have reached greater heights as time passes. This context leads to a situation where these slender structures become sensitive to the dynamic effects of wind loads, case in which the human comfort is often the prevailing criterion for the structural design. This paper addresses criteria from finite element modelling, modal truncation, wind directionality, and comfort assessment applied to two building studies (buildings A and B) subjected to wind tunnel testing. Then, the impact of structural design criteria on many different disciplines is exposed, establishing a comparison between different criteria. This investigation intends to bring precision to the procedure, while creating a reliable set of criteria to perform an assessment of the dynamic response from the wind tunnel testing of tall buildings.